Histoplasma capsulatum Glycans From Distinct Genotypes Share Structural and Serological Similarities to Cryptococcus neoformans Glucuronoxylomannan - Gonçalves, Diego de Souza; Rodriguez de La Noval, Claudia; Ferreira, Marina da Silva; Honorato, Leandro; Araújo, Glauber Ribeiro de Sousa; Frases, Susana; Pizzini, Claudia Vera; Nosanchuk, Joshua D.; Cordero, Radames J. B.; Rodrigues, Marcio L.; Peralta, José Mauro; Nimrichter, Leonardo; et al. (Frontiers in Cellular and Infection Microbiology, 2021)
The cell wall is a ubiquitous structure in the fungal kingdom, with some features varying depending on the species. Additional external structures can be present, such as the capsule of Cryptococcus neoformans (Cn), its major virulence factor, mainly composed of glucuronoxylomannan (GXM), with anti-phagocytic and anti-inflammatory properties. The literature shows that other cryptococcal species and even more evolutionarily distant species, such as the Trichosporon asahii, T. mucoides, and Paracoccidioides brasiliensis can produce GXM-like polysaccharides displaying serological reactivity to GXM-specific monoclonal antibodies (mAbs), and these complex polysaccharides have similar composition and anti-phagocytic properties to cryptococcal GXM. Previously, we demonstrated that the fungus Histoplasma capsulatum (Hc) incorporates, surface/secreted GXM of Cn and the surface accumulation of the polysaccharide enhances Hc virulence in vitro and in vivo. In this work, we characterized the ability of Hc to produce cellular-attached (C-gly-Hc) and secreted (E-gly) glycans with reactivity to GXM mAbs. These C-gly-Hc are readily incorporated on the surface of acapsular Cn cap59; however, in contrast to Cn GXM, C-gly-Hc had no xylose and glucuronic acid in its composition. Mapping of recognized Cn GXM synthesis/export proteins confirmed the presence of orthologs in the Hc database. Evaluation of C-gly and E-gly of Hc from strains of distinct monophyletic clades showed serological reactivity to GXM mAbs, despite slight differences in their molecular dimensions. These C-gly-Hc and E-gly-Hc also reacted with sera of cryptococcosis patients. In turn, sera from histoplasmosis patients recognized Cn glycans, suggesting immunogenicity and the presence of cross-reacting antibodies. Additionally, C-gly-Hc and E-gly-Hc coated Cn cap59 were more resistant to phagocytosis and macrophage killing. C-gly-Hc and E-gly-Hc coated Cn cap59 were also able to kill larvae of Galleria mellonella. These GXM-like Hc glycans, as well as those produced by other pathogenic fungi, may also be important during host-pathogen interactions, and factors associated with their regulation are potentially important targets for the management of histoplasmosis.